2016
DOI: 10.3344/kjp.2016.29.2.110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nefopam on Postoperative Fentanyl Consumption: A Randomized, Double-blind Study

Abstract: BackgroundNefopam is a non-opioid, non-steroidal, centrally acting analgesic drug. The concomitant use of opioids and nefopam is believed to have many advantages over the administration of opioids alone for postoperative pain management. We conducted a randomized, double-blind study to determine the fentanyl-sparing effect of co-administration of nefopam with fentanyl for postoperative pain management via patient controlled analgesia (PCA).MethodsNinety female patients who underwent laparoscopic total hysterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
(53 reference statements)
1
30
0
Order By: Relevance
“…27 Several studies have demonstrated the anti-nociceptive effects of nefopam using a variety of routes of administration and for various indications. [9][10][11][28][29][30] Nefopam reduced thermal hypersensitivity after acute and postoperative pain in rats. 31 Intraperitoneal nefopam showed an antiallodynic effect mediated by adenosine triphosphate-sensitive potassium channel in rats with spinal nerve ligation-induced neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have demonstrated the anti-nociceptive effects of nefopam using a variety of routes of administration and for various indications. [9][10][11][28][29][30] Nefopam reduced thermal hypersensitivity after acute and postoperative pain in rats. 31 Intraperitoneal nefopam showed an antiallodynic effect mediated by adenosine triphosphate-sensitive potassium channel in rats with spinal nerve ligation-induced neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 26 ] However, the incidence of PONV was often not reduced by opioid-sparing strategies with nefopam, as reported in several randomized trials. [ 1 , 13 , 14 ] Furthermore, a few studies have even showed a relatively frequent PONV incidence in patients treated with nefopam,[ 12 , 27 ] suggesting that nefopam is emetic. A previous systematic review showed nefopam was not significantly associated with PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al found that the combined use of nefopam and fentanyl in IV PCA significantly reduced fentanyl consumption after laparoscopic hysterectomy, but pain scores and the incidence of PONV was not significantly decreased in the nefopam group. [ 14 ] Jin et al also showed that total PCA fentanyl consumption was reduced by the combined use of nefopam in PCA after laparotomy; however, the incidence of PONV showed no significant difference between the fentanyl and nefopam-fentanyl combination groups. [ 13 ] Our cohort study also showed that the combined use of nefopam with fentanyl in IV PCA after gynecological surgery resulted in comparable pain scores and no increase in the incidence of PONV compared with the ketorolac-fentanyl combination.…”
Section: Discussionmentioning
confidence: 99%
“…Moon and colleagues18 investigated the opioid-sparing effects of either 200 mg or 400 mg nefopam when added to a fentanyl intravenous PCA over the first 48 postoperative hours. Cumulative on-demand fentanyl consumption during the first 48 hours postoperatively was 236±128 μg vs 107±105 μg for the fentanyl-only versus the fentanyl-nefopam group, while pain scores, side effects, and patient satisfaction were not different 18…”
Section: Resultsmentioning
confidence: 99%